A Victory for International Rule of Law? Or: All's Well that Ends Well?: The 2017 ASP Decision to Amend the Kampala Amendment on the Crime of Aggression. (29th March 2018) - Zimmermann, Andreas
Abstract: On 14 December 2017, the Assembly of States Parties of the Rome Statute decided to activate the International Criminal Court's jurisdiction over the crime of aggression. In doing so, it however seems to have rescinded the Kampala amendment adopted in 2010, and in particular, the need for State Parties to eventually opt out from the Court's aggression-related jurisdiction. This reversal, while being more in line with the Rome Statute than the Kampala amendment itself, raises new (and old) and challenging legal questions which are highlighted in this article.